Tuberculosis Patients Opinion for Directly Observed Treatment Short-Course (DOTS) Programme of Nepal (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Background : DOTS is the most effective strategy available today for tuberculosis control. Objectives : To find out patients knowledge and opinion about DOTS programme of Nepal. Methods : The prospective study was conducted in tuberculosis patients attending DOTS programme in Nepal. Questionnaires are used to collect patient knowledge and opinion. Results : Tuberculosis was most (73%) commonly found in economically active age group (21-50 years old). The incidence of tuberculosis was found higher in male than in female, most of them were married (55%). Tuberculosis cases were commonly found in rural areas 59%, most of them were illiterate 27% and farmers 23.6% respectively. Majority of patients (72%) family size was large 5-7 persons. Knowledge about DOTS programme, majority of the patients (58.3%) answered correctly. The patient's opinion for improving DOTS programme of Nepal, most of them (26.6%) suggested to educate the TB patients and their family members about tuberculosis (method of transmission, dose and side effects of medicine, suitable method for disposable of sputum and other materials and what are the consequences, if drug doses are not completed), 20% of the respondents were of the view that the medicine for tuberculosis should be made available in each and every health care units, 17.6% suggested that according to patients problem drug should be allowed to bring home for one month, 10% suggested to improve behavior of health care workers, 7.3% suggested government should provide free balance diet along with free medicine, 5% suggested make more publicity and 13.3% of patients had no suggestion they thought it was satisfactory. Conclusion : To improve the efficacy of DOTS programme, along with free medicine and directly observed treatment, Tuberculosis control authority should design health education programme for patients, family members and community people such as mode of transmission, preventive methods of tuberculosis and consequences of incomplete treatment. Key words : DOTS; TB; Knowledge DOI: 10.3126/saarctb.v6i1.3063 SAARC J. Tuber. Lung Dis. HIV/AIDS 2009 VI (1) 39-45